Peran Kartu Huruf Terhadap Kemampuan Membaca Awal Anak Usia Dini - Ann Hazzeltine Mau Tellu; Mamy Elisabeth Natbais; Yetri Triwira Neolaka; Sefrianti Tanaem; Maria I.M. Hetmina; Hariyeta M.G. Banunaek; Fredericksen Victoranto Amseke (FKIP UNSULTRA, 2026)
Early reading ability is an important part of early childhood language development that needs to be optimally stimulated through learning activities that are appropriate to children’s developmental characteristics. This study aimed to determine the effect of using letter card media and picture media on the early reading ability of children aged 4–5 years. This research employed a quantitative approach. The sampling technique used was purposive sampling, involving children aged 4–5 years. The respondents consisted of 15 children aged 4–5 years at PAUD Hosana Sungkaen. Data were collected using a questionnaire, with letter card media as the instrument to measure early reading ability. The data analysis technique used was simple linear regression analysis. The findings showed that the use of letter card media contributed 9.2% to the early reading ability of children aged 4–5 years, indicating that better use of letter card media can improve early reading ability in early childhood. Therefore, it is expected that letter card media can be applied appropriately and continuously to support the improvement of early reading ability in early childhood.